Washington's High-Ability Programs During the No Child Left Behind Era. (December 2019) - Hodges, Jaret; Lamb, Kristen
This study used historical data to find associations between changes in policies, funding, and accountability stemming from No Child Left Behind and the provision of services offered to students identified as gifted in the state of Washington. Descriptive statistics and a regression model are used to examine the change in gifted programs by school districts from 2006 to 2007 up until the point where the state received a waiver (2012–2013). Initial results suggest that, during this time frame, the number of districts reporting having gifted programs declined from 77% to 62% of school districts. Furthermore, the regression results provide evidence that school districts that did not make adequate yearly progress were more likely to no longer report having a gifted program as time progressed (β = −0.29, SE = .11). Those districts that retained gifted programs expanded program options.